DFT analysis of the [3 + 2] heterocyclization reaction of ((1,2,4-triazole(1,3,4-oxadiazole)-3(2)-yl)methyl)thiopyrimidines - Yu. V. Karpenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2025)
The article examines the mechanisms of the heterocyclization reaction using density functional theory (DFT) methods. A quantum-chemical analysis of the starting compounds, transition states, and products was conducted, with energy barriers and key reaction stages identified. Particular attention was given to the influence of electronic and steric effects on the stability of the resulting heterocycles. The application of solvent models (PCM) allowed for more realistic simulation of reaction conditions. The study’s findings provide a deeper understanding of chemical transformations in heterocyclic systems and can be utilized to optimize synthetic methods in medicine, agrochemistry, and materials science.